Tuning the Innate Immune Response to Cyclic Dinucleotides by Using Atomic Mutagenesis. (8th June 2020) - Li, Yao; Fin, Andrea; Rovira, Alexander R.; Su, Yichi; Dippel, Andrew B.; Valderrama, Jonathan Andrés; Riestra, Angelica M.; Nizet, Victor; Hammond, Ming C.; Tor, Yitzhak
Abstract: Cyclic dinucleotides (CDNs) trigger the innate immune response in eukaryotic cells through the stimulator of interferon genes (STING) signaling pathway. To decipher this complex cellular process, a better correlation between structure and downstream function is required. Herein, we report the design and immunostimulatory effect of a novel group of c‐di‐GMP analogues. By employing an "atomic mutagenesis" strategy, changing one atom at a time, a class of gradually modified CDNs was prepared. These c‐di‐GMP analogues induce type‐I interferon (IFN) production, with some being more potent than c‐di‐GMP, their native archetype. This study demonstrates that CDN analogues bearing modified nucleobases are able to tune the innate immune response in eukaryotic cells. Abstract : Back to base : Cyclic dinucleotides (CDNs) play critical regulatory roles in bacteria and trigger the innate immune response in eukaryotic cells. Here we illustrate that a systematic modification of the nucleobases, rather than the phosphate or sugar moieties, can generate STING agonists that demonstrate strong immunostimulatory effects.